Analisis Penerapan Akuntansi Lingkungan Berdasarkan Teori Hansen Dan Mowen Pada Rumah Sakit Umum Daerah Pasaman Barat: Studi Kasus Dan Implikasinya - Bina Kurnia; Zulhelmi Zulhelmi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research ismotivated by theproblem that hospitals still have minimal knowledge of environmental accounting because it is relatively new and thereis no specific report regardingenvironmental accounting at the RumahSakit Umum Daerah PasamanBarat. The aim ofthis research is to determinethe application of environmental accounting based on Hansen and Mowen's theory at the Rumah Sakit Umum Daerah Pasaman Barat in 2022.The dataanalysis method inthis research uses descriptivequalitative analysis. The data collection techniques used were observation, interviews, literature study and documentation. The analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this research are that at the Rumah Sakit Umum Daerah Pasaman Barat, in allocating environmental costs, there areseveral things thatare in accordance withPSAK 2015 No.1, namely Identification, Recognition and Measurement, but there are still severalthings that are notin accordance withPSAK 2015 No. 1, namely Presentation of Financial Reports and Disclosure of Financial Reports. The environmental cost categories allocated by the Rumah Sakit Umum Daerah Pasaman Barat are appropriate based on Hansen and Mowen's theory, this is proven by the expenditure of appropriate waste-related costs based on theclassification of environmental accountingcosts based on Hansen andMowen's theory, namely prevention costs, detection costs, costs internalfailure, and externalfailure costs.